Use of CRISPER for Gene Editing in Mosquito that Transmit Malaria - Qurat-ul-Ain; Ishaq, Fatima; Tariq, Uzma; Saqib, Muhammad; Ali, Mubashar; Qalandar, Shahbaz; Faisal, Muhammad; Mobeen, Asifa; Arsalan, Muhammad; Ajaz, Rahmeen (Indus Journal of Bioscience Research, 2024)
Malaria is one of global silent and thoughtful medical concern, caused by Plasmodium parasites which is spread via the bites of female mosquitos specifically Anopheles gambiae. In spite of current and advanced vector control measures and therapeutic precautions, the development of insecticide-resistant mosquitoes encourages the requirement for new approaches for its management like herbal products or gene-editing. CRISPR/Cas9, a new genome-manipulating technique, provides incomparable precision and competence for genetic modulation that makes it a promising option for suppressing malaria-carrying populations of mosquito. The CRISPR/Cas9 system contains of the Cas9 nuclease and a guide RNA, which work collectively to make alterations in targeted DNA. In mosquitos, this technique has been used to decrease number of malarias spreading vectors by targeting its productiveness or viability genes. Active transport of CRISPR/Cas9 composite into mosquito cells is crucial for effective gene editing, and more than a few techniques have been developed and improved. Microinjection is a frequently employed method that contains injecting Cas9 protein, mRNA, and guide RNA straight into embryos of vector. Receptor-Mediated Ovary Transduction of Cargo, which updates the transfer procedure by inserting Cas9-peptide complexes into adult female mosquitos. These short-proteins fix to specific ovary receptors, permitting the carriage for removal. Improving CRISPR/Cas9 delivery methods is important for actual and active gene editing in vector mosquitos. These advances can aid to shape effective preventive measures.